RELAXIN: A MAGICAL THERAPY FOR HEALTHY HEART - Waza, Ajaz Ahmad; Bhat, Shabir Ahmad; Hamid, Zeenat (International Journal of Current Pharmaceutical Research, 2018)
Relaxin (a peptide hormone) has emerged as a cardioprotective agent and plays a vital role in normal cardiac function. By activation a complex network of signaling cascade, relaxin is responsible for creating a healthy environment for heart functioning. Under pathological conditions, such as cardiomyopathy and heart failure, expression level of relaxin is increased dramatically to protect heart. By promoting angiogenesis, vasodilatation, improving ischemia/reperfusion injury and remodeling, relaxin has emerged as a magical agent to address cardiac abnormalities. Over the past 3 decades, various cardioprotection strategies are in use to deal with cardiac diseases, however till date no effective therapy is in clinical practice. Relaxin has emerged as a novel therapeutic agent to have beneficial action during various pathological conditions. In this review, we have discussed different cardioprotective roles of relaxin that marks it, as an effective agent to tackle heart related diseases.Â